Developing a quality-based supplier selection model from the buying company perspective. Issue 3 (4th May 2021) - Chen, Kuen-Suan; Chung, Leanne; Chang, Tsang-Chuan
ABSTRACT: In the face of increased competition and globalization, supply chain management has become a crucial aspect of securing competitive advantage. Within this, the quality offered by suppliers is vital. Thus, in this paper, we develop a model to select the best supplier based on process quality from the perspective of the buyer. We first employ the process capability index S p k, which can provide an exact measure of process yield, to evaluate the process quality of suppliers. However, S p k must be estimated from preliminary samples or obtained subsamples. This increases uncertainty and can lead to miscalculation. To ensure the reliability of assessment, we derive the lower confidence limit of S p k to serve as a standard of process quality assessment and construct a process capability analysis chart to select the best supplier. The chart also provides recommendations for process improvement to serve as a reference for suppliers with poor performance. Finally, we present two real-world case studies to demonstrate the practical applicability of the proposed method.